2017
DOI: 10.1080/07347332.2016.1276503
|View full text |Cite
|
Sign up to set email alerts
|

Managing cancer and employment: Decisions and strategies used by breast cancer survivors employed in low-wage jobs

Abstract: Advances in breast cancer screening and treatment have led to an overall 5-year survival rate of 90%. Many of these cancer cases are diagnosed in working women. Few studies have explicitly examined the cancer–work interface, as experienced by low-wage earning women with breast cancer. This study uses in-depth, semistructured interviews with 24 low-wage breast cancer survivors to identify employment decisions and factors that influenced or enabled these decisions, and examine the individual strategies and workp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 31 publications
3
27
0
1
Order By: Relevance
“…These results are in keeping with prior literature and are unsurprising, because even out‐of‐pocket costs incurred for cancer treatment and lost wages can be quite significant . In addition, similar to recent research, employer accommodations were credited with playing a considerable role in enabling survivors to remain employed throughout treatment initiation. Survivors described key accommodations including flexible schedules, leave allowances to attend appointments, and telecommuting options.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results are in keeping with prior literature and are unsurprising, because even out‐of‐pocket costs incurred for cancer treatment and lost wages can be quite significant . In addition, similar to recent research, employer accommodations were credited with playing a considerable role in enabling survivors to remain employed throughout treatment initiation. Survivors described key accommodations including flexible schedules, leave allowances to attend appointments, and telecommuting options.…”
Section: Discussionsupporting
confidence: 86%
“…Early detection and improved treatment options have enabled many cancer survivors to decrease the amount of time spent out of the workforce after a cancer diagnosis, with a growing number of survivors opting to work throughout treatment . Minimizing the impact of a cancer diagnosis and treatment on employment guards against lost income or a disruption of health insurance benefits . For example, a recent population‐based analysis of employment outcomes among cancer survivors found that within the first year of diagnosis, employed survivors lost an average of 5 weeks' worth of paid work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 14.5 million men and women were living beyond their cancer diagnosis in 2014, and by 2024, this number is expected to increase to 19 million . With 72.5% of new of cases in working‐age adults between the ages of 20 and 74, many survivors are likely to be employed when they are diagnosed with cancer and are likely to return to work posttreatment or continue to work during treatment …”
Section: Introductionmentioning
confidence: 99%
“…To date, the experiences of survivors employed in low‐wage jobs have been understudied . This is a critical omission in the scientific literature because low‐wage employment is highly prevalent in the US economy, and the characteristics of occupations that pay low wages have been overlooked as a possible contributor to adverse employment outcomes among cancer survivors . Given that there is no universally accepted definition of low‐wage work, for the remainder of this paper, we adopt the general term of working poor to refer to survivors who are employed in jobs with earnings that fall below 200% of the poverty line…”
Section: Introductionmentioning
confidence: 99%